VSC with direct PI power control for frequency compensation in a microgrid: A PBC approach (2019)
The power systems with low inertia such as microgrids require advanced control strategies to improve their performance. These type of grids use voltage source converters to interconnect renewable energy sources and storage devices. The converters can present complementary ancillary services such as grid frequency response support. This paper uses a passive control strategy for power electronic converters based on direct power control model and presents the strategy to mitigate the fast changes of the dynamic grid frequency response. The real-time simulations validate the application of the method. © 2019 IEEE.